Methods of mathematics applied to calculus, probability, and statistics - Hamming, R. W. 1915-1998 (Dover Publications, 2004)
This text focuses on the most widely used applications of mathematical methods, including those related to probability and statistics. The 4-part treatment begins with algebra and analytic geometry and proceeds to an exploration of the calculus of algebraic functions and transcendental functions and applications. 1985 edition. Includes 310 figures and 18 tables.
Originally published: Englewood Cliffs, N.J. : Prentice-Hall, c1985.
Includes index.
Keywords: Mathematics.; elektronické knihy; electronic books